2018
DOI: 10.1016/j.drugalcdep.2017.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol metabolism in hangover sensitive versus hangover resistant social drinkers

Abstract: Hangover resistant individuals and hangover sensitive drinkers did not significantly differ on BrAC, subjective sleepiness, and subjective intoxication after consuming a moderate amount of alcohol. These findings suggest that drinkers who usually experience hangovers after a heavy drinking occasion do not experience alcohol intoxication differently than hangover resistant drinkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Whereas the majority of drinkers experiences hangovers following an evening of heavy alcohol consumption, a minority of drinkers claim to be hangover resistant [ 2 , 3 ]. Several studies have compared the characteristics of these two groups of drinkers [ 4 , 5 ], in order to further elucidate the pathology of the alcohol hangover. This is a potentially important avenue of research as individual differences in the typology of alcohol hangover may help to understand the pathology of alcohol hangover [ 6 , 7 ], and identify factors that may aggravate or lessen hangover severity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the majority of drinkers experiences hangovers following an evening of heavy alcohol consumption, a minority of drinkers claim to be hangover resistant [ 2 , 3 ]. Several studies have compared the characteristics of these two groups of drinkers [ 4 , 5 ], in order to further elucidate the pathology of the alcohol hangover. This is a potentially important avenue of research as individual differences in the typology of alcohol hangover may help to understand the pathology of alcohol hangover [ 6 , 7 ], and identify factors that may aggravate or lessen hangover severity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data show that this claim heavily depends on how much alcohol drinkers consume, but even at higher eBAC levels a small proportion of drinkers claim not to have hangovers [27,28]. At the same time, other hangover research showed no significant differences between the two groups of drinkers on several biomarkers such as urine ethyl glucuronide (EtG) and ethyl sulfate (EtS) [57] or methanol [58], saliva cytokine levels [59], sensitivity to acute alcohol effects [60], demographics [31], or psychological characteristics such as mental resilience [61]. Additionally, the current study could not differentiate hangover-sensitive and hangover-resistant drinkers based on their dietary nutrient intake.…”
Section: Discussionmentioning
confidence: 99%
“…Data from n = 8 subjects that participated in both an acute alcohol challenge experiment [27] and a hangover study [23] were evaluated to determine if hangover severity was related to the ethanol elimination rate. Subjects were included if they were male or female healthy social drinkers between 18 and 30 years old, reported no physical or mental disease, and were non-alcoholic and/or nondependent drinkers.…”
Section: Methodsmentioning
confidence: 99%
“…The acute study [27] was a controlled experiment in which subjects completed an alcohol challenge to reach a peak BrAC of 0.05%. After arrival at the institute, participants consumed a standardized meal and body weight was determined.…”
Section: Study 1 Assessment Of Ethanol Elimination Rate-acute Studymentioning
confidence: 99%